You must take part in revolution - Chan, Melissa (Street Noise Books, 2025)
It is 2035. The US and China are at war. America is a proto-fascist state. Taiwan is divided into two. As conflict escalates between nuclear powers, three idealistic youths who first met in Hong Kong develop diverging beliefs about how best to navigate this techno-authoritarian landscape. Andy, Maggie, and Olivia travel different paths toward transformative change, each confronting to what extent they will fight for freedom, and who they will become in doing so. A powerful and important book about global totalitarian futures, and the costs of resistance.--